Recent Studies of Pickering Emulsions: Particles Make the Difference. Issue 34 (23rd June 2016) - Wu, Jie; Ma, Guang‐Hui
Abstract : In recent years, emulsions stabilized by micro‐ or nanoparticles (known as Pickering emulsions) have attracted much attention. Micro‐ or nanoparticles, as the main components of the emulsion, play a key role in the preparation and application of Pickering emulsions. The existence of particles at the interface between the oil and aqueous phases affects not only the preparation, but also the properties of Pickering emulsions, affording superior stability, low toxicity, and stimuli‐responsiveness compared to classical emulsions stabilized by surfactants. These advantages of Pickering emulsions make them attractive, especially in biomedicine. In this review, the effects of the characteristics of micro‐ and nanoparticles on the preparation and properties of Pickering emulsions are introduced. In particular, the preparation methods of Pickering emulsions, especially uniform‐sized emulsions, are listed. Uniform Pickering emulsions are convenient for both mechanistic research and applications. Furthermore, some biomedical applications of Pickering emulsions are discussed and the problems hindering their clinical application are identified. Abstract : Pickering emulsions, stabilized by particles, have attracted much attention in recent years. Due to the introduction of particles at the interface between oil and aqueous phases, Pickering emulsions possess many distinctive properties such as high stability and low toxicity, when compared with classical emulsions stabilized by surfactants. These properties also affect their applications, especially in biomedical fields, such as oral or topical delivery systems.